2021
DOI: 10.1186/s41747-020-00197-8
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of flow dynamics in the portal circulation using 320-detector-row computed tomography: a feasibility study

Abstract: Multidetector row computed tomography (CT) scanners perform dynamic scanning and have a wide scan range. Time-resolved three-dimensional CT (i.e., 4D CT) has recently enabled visualization of flow in neurovascular vessels. We hypothesized that 4D CT technology would be a useful and non-invasive method for visualizing the flow dynamics of the portal circulation. The aim of this study was to evaluate the technical feasibility of 4D CT for visualizing flow dynamics in the portal circulation using 320-detector-row… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…The results of this study indicate that even extensive MRI pre-processing and homogenization of the MR images do not sufficiently address the variations in acquisition and reconstruction parameters. This is in line with studies published in recent years that investigated the reproducibility of MRI radiomics features in test-retest phantom data as well as in patient data of varying disease sites, and showed that, among others, the variations in acquisition and reconstruction parameters strongly influence the values (concordance) of radiomics features [ 24 , 27 , 28 , 29 , 49 , 50 , 51 , 52 ]. Shur et al [ 29 ] performed a test-retest 1.5T MRI phantom study using the same imaging protocol and showed that 20% of the examined features were not repeatable.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of this study indicate that even extensive MRI pre-processing and homogenization of the MR images do not sufficiently address the variations in acquisition and reconstruction parameters. This is in line with studies published in recent years that investigated the reproducibility of MRI radiomics features in test-retest phantom data as well as in patient data of varying disease sites, and showed that, among others, the variations in acquisition and reconstruction parameters strongly influence the values (concordance) of radiomics features [ 24 , 27 , 28 , 29 , 49 , 50 , 51 , 52 ]. Shur et al [ 29 ] performed a test-retest 1.5T MRI phantom study using the same imaging protocol and showed that 20% of the examined features were not repeatable.…”
Section: Discussionsupporting
confidence: 90%
“…This is in line with studies published in recent years that investigated the reproducibility of MRI radiomics features in test-retest phantom data as well as in patient data of varying disease sites, and showed that, among others, the variations in acquisition and reconstruction parameters strongly influence the values (concordance) of radiomics features [ 24 , 27 , 28 , 29 , 49 , 50 , 51 , 52 ]. Shur et al [ 29 ] performed a test-retest 1.5T MRI phantom study using the same imaging protocol and showed that 20% of the examined features were not repeatable. A study on repeatability and reproducibility using a T2W pelvic phantom showed that radiomics features values are not only affected by varying acquisition parameters but also by the use of different MRI vendors and magnetic field strengths, wherein the reproducibility of the radiomic features is more affected by difference in MRI vendor than by difference in magnetic field strength [ 49 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Some models are purely based on such a private dataset (e.g. Shamout, Shen, Wu, Kaku, Park, Makino, Jastrzȩbski, Witowski, Wang, Zhang, et al., 2021 , Castiglioni, Ippolito, Interlenghi, Monti, Salvatore, Schiaffino, Polidori, Gandola, Messa, Sardanelli, 2021 , Xia, Chen, Ren, Zhao, Wang, Jin, Zhou, Wang, Yan, Zhang, et al., 2021 ). But many authors utilise small private dataset together with larger public datasets.…”
Section: Resultsmentioning
confidence: 99%
“…The formula is also based on the evaluation formula and features proposed by Taha et al [ 47 ]. In this study, Intersection over Union (IoU) (as known as Jaccard coefficient), Accuracy (ACC), Area Under the ROC Curve (AUC), Dice coefficient, and Average Hausdorff Distance (AVGDIST) [ 48 ] were used as metrics. These metrics can be composed of the following four parameters: TP (true positive), TN (true negative), FP (false positive), and FN (false negative) by means of the values embedded in the segmentation.…”
Section: Resultsmentioning
confidence: 99%